The Modern Experience of Lobbying Interests in Europe - Мамонтова, Елла Вікторівна; Мамонтова, Е. В.; Мамонтова, Элла Викторовна; Mamontova, Ella V.; Бурик, Зоряна Михайлівна; Бурик, З. М.; Buryk, Zoriana M.; Стріха, Людмила Олександрівна; Стріха, Л. О.; Strikha, Liudmyla O.; Вонсович, Сергій Геннадійович; Вонсович, С. Г.; et al. (Universidad de Almería, 2021)
The current experience of lobbying interests in Europe requires a detailed study of legislation to provide open public access to the Transparency Register and to promote the use of lobbying transparency mechanisms in European countries and EU institutions. These mechanisms ensure the implementation of relevant regulations and political decisions by political actors with the assistance of interest groups for the effective implementation of public policy. The purpose of the study is to establish the patterns of implementation of interest lobbying policy in Europe and assessing the reliability of lobbying activities in European countries and EU institutions to check the effectiveness of lobbying interests’ modern experience in Europe and mechanisms in ensuring transparency and its integrity in the EU. Research methods: comparative analysis; regression analysis; systematization, generalization. Results. Availability has established the relationship between disclosure by lobbyists and oversight of compliance with the rules of the register and transparency in lobbying. Lobby transparency has been identified as too weak across Europe, as the implementation of the Transparency Register, which aims to regulate lobbying, has not protected against its excessive influence. The largest expenditure on EU lobbying for the period 2017-2018 falls on countries such as Belgium, Germany, and Italy. The current expenditure of EU member states is 91%, more than €2 billion. It was found that lobbying in Europe helps to solve current problems by further improving the legislation that will ensure the implementation of effective EU policy, where the main topics on the agenda are the implementation of the Law on Digital Services and overcoming the COVID-19 pandemic. It has been established that lobbying in Europe should address barriers to access to public sector information and public data faced by citizens, and require the implementation of measures to regulate the further activities of officials between the public sector and lobbying.

Сучасний досвід лобіювання інтересів у Європі вимагає детального вивчення законодавства для забезпечення відкритого доступу громадськості до Реєстру прозорості та сприяння використанню механізмів прозорості лобіювання в європейських країнах та інституціях ЄС. Ці механізми забезпечують виконання політичними акторами відповідних нормативних актів та політичних рішень за сприяння груп інтересів для ефективної реалізації державної політики. Метою дослідження є встановлення закономірностей реалізації політики лобіювання інтересів у Європі та оцінка надійності лобістської діяльності в європейських країнах та інституціях ЄС для перевірки ефективності сучасного досвіду лобіювання інтересів у Європі та механізмів забезпечення прозорості та її прозорості. цілісності в ЄС. Методи дослідження: порівняльний аналіз; регресійний аналіз; систематизація, узагальнення. Результати. Доступність встановила взаємозв’язок між розкриттям лобістами та наглядом за дотриманням правил реєстру та прозорістю лобіювання. Прозорість лобіювання була визначена як занадто слабка в Європі, оскільки впровадження Реєстру прозорості, що має на меті регулювати лобіювання, не захистило від його надмірного впливу. Найбільші витрати на лобіювання в ЄС у період 2017-2018 років припадають на такі країни, як Бельгія, Німеччина та Італія. Поточні витрати країн-членів ЄС становлять 91%, більше ніж 2 мільярди євро. Виявлено, що лобіювання в Європі допомагає вирішувати актуальні проблеми шляхом подальшого вдосконалення законодавства, яке забезпечить реалізацію ефективної політики ЄС, де основними темами порядку денного є імплементація Закону про цифрові послуги та подолання пандемії COVID-19. Встановлено, що лобіювання в Європі має усунути перешкоди доступу громадян до інформації державного сектору та публічних даних, з якими стикаються громадяни, та вимагати впровадження заходів щодо регулювання подальшої діяльності посадових осіб між державним сектором та лобізмом.
Mamontova E. The Modern Experience of Lobbying Interests in Europe / E. Mamontova, Z. Buryk, L. Strikha, S. Vonsovych, T. Voropayeva, O. Baranova // Estudios de Economía Aplicada, Vol.: 39 Issue: 8: Sustainable Economic Development: Pattern and Perspective : Monograph. - Universidad de Almería, 2021. DOI: https://doi.org/10.25115/eea.v39i8.6203
Keywords: lobbyists; lobbying; lobbying of interest; lobbying activity; lobbyists registers; transparency register; EU institutions; EU countries; European Union; integrity mechanisms; technology companies; лобісти; лобіювання; лобіювання інтересів; лобістська діяльність; реєстри лобістів; реєстр прозорості; інституції ЄС; країни ЄС; Європейський Союз; механізми доброчесності; технологічні компанії; Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Political science